Correlating Artepillin C cytotoxic activity on HEp-2 cells with bioinspired systems of plasma membranes - Kobal, Mirella B. [UNESP]; Pazin, Wallance M. [UNESP]; Bistaffa, Maria J. [UNESP]; Constantino, Carlos J.L. [UNESP]; Toledo, Karina A. [UNESP]; Aoki, Pedro H.B. [UNESP] (Elsevier, 2020)
Artepillin C is the main compound present in propolis from Baccharis dracunculifolia, whose antitumor activity has been the focus of many studies. Herein, we shall investigate the Artepillin C mechanisms of action against cells derived from the oropharyngeal carcinoma (HEp-2). Cytotoxicity tests revealed that the concentrations of Artepillin C required to reduce cell viability by 50% (CC50) are dependent on the incubation time, decreasing from 40.7 × 10−5 mol/L to 15.7 × 10−5 mol/L and 9.05 × 10−5 mol/L considering 12, 24 and 48 h, respectively. Hydrophobic interactions on neutral species of Artepillin C induce aggregation over the HEp-2 plasma membrane, given the acid conditions of the cellular culture. Indeed, Langmuir monolayers mimicking cellular membranes of tumor cells revealed Artepillin C affinity to interact with 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) containing 20 mol% of 1,2-dipalmitoyl-sn-glychero-3-phosphoserine (DPPS), leading aggregation on giant unilamellar vesicles (GUVs) at pH 3.2. Moreover, leakage experiments on GUVs have shown that the presence of DPPS enhances the efflux of the fluorescent probe signaling the membrane permeabilization, which is the origin of the necrotic pathway triggered in HEp-2 cells, as observed by flow cytometry assays.
Keywords: Artepillin C; Green propolis; GUVs; Model membranes; Oropharyngeal carcinoma cells